Sexual and reproductive health from the perspective of patients with autoimmune rheumatic diseases in Mexico: a qualitative study - Skinner Taylor, Cassandra Michelle; Pérez Barbosa, Lorena; Lujano Negrete, Abraham Yair; Arévalo Nieto, Fany Rocío; Corral Trujillo, María Eugenia; Aguilar Leal, Andrea; Sandoval Torres, Génesis Guadalupe; Rodríguez Ruiz, Cecilia; Rios Medina, Melanie Gabriela; Manrique de Lara, Amaranta; Galarza Delgado, Dionicio Ángel; Peláez Ballestas, Ingris (BMJ Journals, 2025)
Objectives. To explore the experiences and perspectives of female patients with autoimmune rheumatic diseases (ARDs) regarding sexual and reproductive health, including contraception, family planning, and pregnancy. Design. Qualitative descriptive study using semistructured interviews. Setting. Specialised rheumatology clinic in a tertiary hospital in Monterrey, Mexico. Participants 21 female patients aged 18–49 with a confirmed ARD diagnosis who were receiving care at the clinic. Participants. Were selected using convenience sampling, ensuring diversity in age, disease type and stage, socio-economic and cultural background, sexuality and disability status. All participants completed the study. Results. Four main themes emerged from the analysis. First, participants expressed confusion and concern about the safety and effectiveness of contraceptive methods in the context of their disease and treatment. Second, many participants shared anxiety about infertility, heredity and the risks of pregnancy associated with their ARDs, leading to uncertainty in pregnancy planning. Third, there was concern about the safety of medications during pregnancy and breastfeeding, indicating a lack of guidance and information from healthcare providers. Lastly, patients often deferred decision-making about contraception and medication to their rheumatologists but recognised the importance of a multidisciplinary care approach for comprehensive sexual and reproductive health management. Conclusions. The study revealed that women with ARDs experience significant challenges and unmet needs related to sexual and reproductive health, particularly in understanding safe contraception, pregnancy planning and medication use during pregnancy and lactation. These findings emphasise the need for rheumatologists to provide clearer guidance on these issues and collaborate closely with gynaecologists and other specialists to ensure comprehensive, patient-centred care. Enhancing communication and education strategies in rheumatology consultations could address these gaps and improve the sexual and reproductive health outcomes and decisionmaking processes of women with ARDs.